The Baker Street jurors - Robertson, Michael, 1951- (Robertson, Michael, 1951- Baker Street mystery, 2016)
"Michael Robertson has delighted mystery readers and Sherlock Holmes aficionados everywhere with his charming and innovative Baker Street mystery series, where brothers Reggie and Nigel Heath are charged with answering letters to Sherlock that arrive at their law office, located at 221B Baker Street. In the exclusive London suburb of Hampstead Heath, Rory McSweeny--a true national hero, having led the England cricket team to successive international championships--is accused of murdering his own wife with his own cricket bat. As preparations are made for the trial, the Royal Mail delivers two jury summonses to a law chambers located at Dorset House in the two hundred block of Baker Street. One summons is addressed to Nigel Heath. The other is addressed to Sherlock Holmes. And because Baker Street Law Chambers encompasses the address 221B Baker Street, both letters end up on Nigel's desk. There are twelve empaneled jurors--plus the alternates. But, an unfortunate accident befalls one of the jurors. And then things get worse. Jurors are dropping like flies, and they don't know who is doing it or why--or which of them will be next"--